2016
DOI: 10.1186/s40794-016-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, practices and perceptions of trachoma and its control among communities of Narok County, Kenya

Abstract: BackgroundTrachoma is the leading infectious cause of blindness in the world. It is commonly found in cultural groups with poor hygiene. Trachoma control includes Surgery, Antibiotics, Facial cleanliness and Environmental Improvement (SAFE). Potentially blinding and active trachoma are monitored using trachomatous trichiasis (TT) in adults and trachoma inflammation-follicular (TF) in children aged 1–9 years respectively. A cross-sectional study to assess the knowledge, practices and perceptions of trachoma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…The participants responded that trachoma can be prevented by using latrine, improve environmental sanitation, not using common towel, and washing hand and face with soap. Having knowledge on washing face, not sharing towels, and environmental sanitation was important on prevention of trachoma infection [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants responded that trachoma can be prevented by using latrine, improve environmental sanitation, not using common towel, and washing hand and face with soap. Having knowledge on washing face, not sharing towels, and environmental sanitation was important on prevention of trachoma infection [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The odds of good attitudes on trachoma prevention and control among participants who had ever received health education were 2.1 times higher than participants who had not ever received health education about trachoma. Health education can help reducing misconceptions and changing cultural perceptions of communities on trachoma prevention and control [ 11 , 27 ]. Effective health education is the key to building the favorable attitudes on trachoma prevention and control among communities to achieve the goal of eliminating trachoma as a public health problem [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high inter-observer agreement was attributed to strict recruitment criteria and prolonged apprenticeship period. A study conducted in Narok revealed that lay people can identify [ 12 ] which means that this task can be shifted even to unskilled workers. The World Health Organization standard trachoma guidelines do not recommend mandatory validation of TT graders [ 1 , 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2010 and 2014 impact surveys indicated that only 2 southern segments ( Figure 1 ) had remained endemic due to high prevalence of known environmental risk factors [ 11 ]. A survey segment was defined as an area with 100,000-200,000 people [ 12 ].These population size limits were within the limits of the trachoma intervention unit recommended by the World Health Organization [ 1 ]. The 2014 impact survey report indicated that the prevalence of TT in people 40+ years old in the two segments was 5.9%(95% CI: 4.0%-7.7%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation